ROLES OF PREPARATION METHOD ON CHARACTERISTICS OF SUPRAMOLECULAR-STRUCTURED POLYMER ELECTROLYTE MEMBRANE FUEL CELL BASED ON SULFONATED POLYSTYRENE - Sunit Hendrana; Morina Septiviani Semboor; Christi Liamita Natanael; Iman Rahayu; Mashadi Mashadi; Sudirman Sudirman (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2017)
Polymer Electrolyte Membrane Fuel Cell with supramolecular structure based on Sulfonated Polystyrene (S-PS) have been developed in Research Centre for Physics LIPI. In forming the supramolecular structure sulfonate groups in S-PS are aligned with polyethylene-graft-maleic anhydride (PE-g-MA) which carried out by dissolution of the constituent and mixing of both. The alignmentof sulfonate groups in s-PS is carried out in a liquid form.Therefore, in this study, the effect of concentration of the solution of both polymersconstituent to the alignment of the sulfonate groups and the characteristics of the membrane produced is studied. Scanning Electron Microscope (SEM) images show that all membranes prepared are rigid. Differential Scanning Calorimetry (DSC) studied show very significance differences in its crystal sizes. XRD diffraction data also support the previous results. Membrane prepared from very dilute solution having better ion exchange capacity (IEC), water uptake and ionic conductivity. Therefore, the experiments results showing that very low concentration of polymer constituent, clearly, produced better interaction of both, which agree with hyphotesis in this work where supramolecular structure can be formed by mixing two very dilute polymer solutions.